Microbial microleakage assessment of class V cavities restored with different materials and techniques: A laboratory study - Hossein Nematollahi; Ali Bagherian; Kiarash Ghazvini; Habibollah Esmaily; Mina Azadegan Mehr (Wolters Kluwer Medknow Publications, 2017)
Background: The aim of this study was to compare microbial microleakage of class V cavities restored with different materials and techniques using a microbial leakage assessment method. Materials and Methods: One hundred extracted, caries-free, human maxillary premolars were randomly divided into five groups. Group 1: Resin-modified glass ionomer (RMGI), Group 2: Closed sandwich with flowable composite + nanohybrid composite, Group 3: Nanohybrid composite, Group 4: Closed sandwich with RMGI + nanohybrid composite, and Group 5: Flowable composite + nanohybrid composite that were co-cured together ("snow-plow" technique). A microbial penetration method utilizing Streptococcus mutans as an indicator was tested for leakage assessment. Data were analyzed and the significance level was α =0.05. Results: The log-rank test indicated a statistically significant difference in leakage rates among the five groups (P = 0.008). Mantel-Cox log-rank test indicated statistically significant differences in microleakage rates between Groups 1 and 3 (P = 0.029), between Groups 2 and 5 (P = 0.005), and between Groups 3 and 5 (P = 0.002). Conclusion: With respect to the limitations of an in vitro study, our findings suggest that adding a thin layer of flowable composite or RMGI under nanohybrid composite in class V cavities did not decrease the bacterial leakage rate, whereas use of the "snow-plow" technique caused an increase in the microleakage rate.